Yovhan Oskeberan ew ir "Matt̕êi meknowt̕iwn"ẹ - P̕ayaslean, Zareh 1915-1963 (Kilikioy Kat̕oġikosowt̕ean arxiwner, 2003)
The biography and activities of Saint John Chrysostom's d. 407, and analysis of his interpretation of the Gospel of Saint Mathew